Educational Gradients and Pathways of Disability Onset Among Older Mexicans. (April 2016) - Saenz, Joseph L.; Wong, Rebeca
Introduction: Educational disparities research is less common in developing countries. We evaluate whether educational gradients of disability onset exist in Mexico across groups (birth cohort and sex) and whether the association is unexplained or indirect via health (health behaviors, chronic conditions, and self-rated health) or economic (income, wealth, and health insurance) pathways. Method: Data come from the Mexican Health & Aging study. Activities of daily living are reported in 2001, 2003, and 2012 by respondents and spouses aged 50+ ( N = 9, 560). Groups are analyzed using logistic regression to test education–disability onset associations. Results: Significant education–ADL onset associations were observed across groups, and much of these associations were direct (unexplained by pathways). Indirect effects operated primarily through the health pathway. Discussion: Those with less education were disadvantaged in terms of disability across birth cohorts and sex. Unexplained effects of education may suggest unobserved mediators or differential returns to resources by educational level.